2011
DOI: 10.2147/ppa.s17317
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to cervical cancer screening in Mulanje, Malawi: a qualitative study

Abstract: Background:In Malawi, cervical cancer is the most prevalent form of cancer among women, with an 80% mortality rate. The Mulanje Mission Hospital has offered free cervical cancer screening for eight years; however, patients primarily seek medical help for gynecologic complaints after the disease is inoperable.Methods:We investigated how women in rural Malawi make health-seeking decisions regarding cervical cancer screening using qualitative research methods. The study was conducted between May and August of 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
128
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(145 citation statements)
references
References 4 publications
(3 reference statements)
17
128
0
Order By: Relevance
“…High Coverage of the target population by screening test and treatment of all women with abnormal lesions represent the most important factors in determining program success, and are the immense practical challenges (Wongwatcharanukul et al, 2014). Challenges faced by the patients and health care providers in cervical cancer issue can be affected early detection practices (Fort et al, 2011).…”
Section: Roghieh Bayramimentioning
confidence: 99%
“…High Coverage of the target population by screening test and treatment of all women with abnormal lesions represent the most important factors in determining program success, and are the immense practical challenges (Wongwatcharanukul et al, 2014). Challenges faced by the patients and health care providers in cervical cancer issue can be affected early detection practices (Fort et al, 2011).…”
Section: Roghieh Bayramimentioning
confidence: 99%
“…This is contrary to a study by Ojiyi and Dike (2008), where the most frequent reason given for not using Pap smear services was lack of physician referral. A qualitative study by Fort, Makin and Siegler (2011) among women in rural Malawi on how they make health-seeking decisions regarding cervical cancer screening revealed that, the major barrier to seeking preventive screening was low knowledge level. This lack of knowledge is contrary to studies by Ajah, Iyoke, Ezeonu, Ugwu, Onoh and Ibo (2015) among 412 secondary school teachers at Abakaliki, Nigeria who found that 75% of respondents were aware of at least one method of cervical cancer prevention.…”
Section: Issn: 2354-2381mentioning
confidence: 99%
“…For example, Malawi attempted a nationwide cytology-based cervical cancer screening program, but it quickly deteriorated due to lack of resources, trained professionals, and infrastructure. [13] There is therefore an urgent need to implement low-cost approaches already available for prevention and early detection of cervical cancer in Sub-Saharan Africa. No study to date, though, has systematically evaluated preferences for prevention and screening, and this information is required to design and implement programs that will result in optimal uptake.…”
Section: Introductionmentioning
confidence: 99%